Cognitive markers for the distinction between asymptomatic and prodromal Alzheimer's disease in Down syndrome: Correlations with volumetric brain changes - Javier García‐Alba; Elisa M. Molanes‐López; Pilar Zuluaga; Cristina Bell‐Fenellos; Lucía Vaquero; Eva Alfayate; Felipe García; Gloria Mateo; Fernando Modenhauer; José M. Galván‐Román; Ricardo Bajo; Alberto Fernández (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Motivated by the difficulties in detecting cognitive deterioration in the context of Down syndrome (DS), we aimed to identify markers of prodromal Alzheimer's disease (AD) in this population. METHODS Sixty‐two participants with DS (age > 45) distributed in three groups (asymptomatic [ADS], prodromal [PDS], and dementia [DDS]) completed the Cambridge Examination for Mental Disorders of Older People with Down's Syndrome and Others with Intellectual Disabilities, Cambridge Cognitive Examination for older adults with Down's Syndrome, and Barcelona Test for Intellectual Disability tests and a magnetic resonance imaging scan. RESULTS Although temporal orientation showed significant differences among groups, only a predictive diagnostic model based on verbal short‐term memory tasks (relying on “cued” recall) allowed the correct classification of 88.5% of ADS, 75.0% of PDS, and 95% of DDS individuals. Cognitive decline strongly correlated with brain volume reductions in orbitofrontal, medial‐temporal, and bilateral thalamus within the DDS group. DISCUSSION Neuropsychological results showed that PDS cases were characterized by a significant deterioration of verbal memory and temporal orientation, compared to ADS. This pattern might be crucial to support diagnosis in clinical settings. Highlights Detecting signs of prodromal dementia is a major challenge in Down syndrome. Such challenge is due to a poor definition of the early cognitive manifestations. Memory tasks relying on “cued” recall allowed the detection of prodromal cases. A pattern of temporal disorientation was also evident in the prodromal phase. These cognitive deficits preceded volumetric brain changes only present in dementia.